(3eNJUQ SjQI YeQ Hf YHO GdYRjRs - (3GHi GdeXaQ eDjO GdOhdI CSGeI Hf eQTO Hf Ydj HfebdO Hf efbPs; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3bGd CSGeI HYO MeO Gddg Effi hbaJ Ydi cJGH efGbH CejQ GdeDefjf YeQ Hf YHO GdYRjR aLQOJg ef GdCSGfjO hMPaJ eG ajg ef GdJcQGQ s
(3BNQgG (B:s
(3hQCjJ QLdkG ef hdO YeQ Hf YHO GdYRjR QVi Gddg Yfg bO Med ai jhe hGMO Ydi eFI aQS ai SHjd Gddg YR hLd BNQ GdcJGH hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3fbdJ ef fSNI SbjeIs
(3ai GdeYgO fSNI CNQi HQbe (B1988 (3JGQjNs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
Keywords: (3GdJGQjNs